The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1460-9568.2000.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in direct current (DC) potentials and infra‐slow EEG oscillations at the onset of the luteinizing hormone (LH) pulse

Abstract: An essential function of the neuroendocrine system lies in the coordination of hypothalamo-pituitary secretory activity with neocortical neuronal activity. Cortical direct current (DC) potential shifts and EEG were monitored in conjunction with the circulating concentration of luteinizing hormone (LH) in humans while asleep to assess a hypothalamic-neocortical interaction. The onset of an LH pulse was accompanied (i) at frontocortical locations by a transient positive DC potential shift of approximately 3 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…Slow oscillations, which were originally discovered by Steriade et al (15,16) using intracellular recordings and were subsequently confirmed in human sleep EEG recordings (17,34,35), grasp the entire thalamocortical system. However, they can be recorded also in isolated slabs of neocortical tissue which, hence, is considered the primary generator structure of these oscillations.…”
Section: Discussionmentioning
confidence: 84%
“…Slow oscillations, which were originally discovered by Steriade et al (15,16) using intracellular recordings and were subsequently confirmed in human sleep EEG recordings (17,34,35), grasp the entire thalamocortical system. However, they can be recorded also in isolated slabs of neocortical tissue which, hence, is considered the primary generator structure of these oscillations.…”
Section: Discussionmentioning
confidence: 84%
“…The slow oscillation can also be identified in the human sleep EEG, in which a spectral peak in power at ∼0.8 Hz is found (Steriade et al 1993;Achermann and Borbély 1997;Marshall et al 2000;Mölle et al 2002). Slow oscillations grasp the entire thalamo-cortical system.…”
Section: Reactivation Of Newly Formed Memories During Sleepmentioning
confidence: 92%
“…Notably, these changes in slow oscillatory and spindle power across the initial sleep cycles are paralleled by distinct changes in the transcortical direct current (DC) potential, which shifts steeply toward negativity over frontocortical sites during transition into SWS. During SWS, this DC-potential negativity is maintained and only slightly decreases toward the end of the period (Marshall et al 1996(Marshall et al , 1998. The time course of DC-potential changes is strongly correlated (with average coefficients r > 0.80) with changes in spindle, delta, and slow oscillatory activity (Marshall et al 2003).…”
Section: Reactivation Of Newly Formed Memories During Sleepmentioning
confidence: 93%
“…A general rule is that higher frequency patterns emerge locally whereas lower frequencies involve larger brain regions. Finally, slow oscillations have been described in numerous brain structures and can occur simultaneously in the neocortex, basal ganglia, limbic system, basal forebrain and the autonomous nervous system (Allers et al, 2000;Marshall et al, 2000;Wichmann et al, 2002;Sirota et al, 2003). However, the wave-by-wave coherence within the ripple diminishes rapidly within a few hundred micrometers (Csicsvari et al, 2000).…”
Section: Relationship Between Various Brain Oscillatorsmentioning
confidence: 99%